Two-step grafting of 2-hydroxyethyl methacrylate (HEMA) and 2-(dimethylamino)ethyl methacrylate (DMAEMA) onto a polyethylene plate for enhancement of Cr(VI) ion adsorption. Issue 7 (21st March 2019) - Yamada, Kazunori; Ishiguro, Yohei; Kimura, Yuji; Asamoto, Hiromichi; Minamisawa, Hiroaki
ABSTRACT: Polyethylene (PE) plates grafted with a neutral monomer, 2-hydroxyethyl methacrylate (HEMA), and a cationic monomer, 2-(dimethylamino)ethyl methacrylate (DMAEMA), (PE-g-PHEMA)-g-PDMAEMA plates were prepared by the two-step photografting. The Cr(VI) ion adsorption behavior of the (PE-g-PHEMA)-g-PDMAEMA plates was investigated as a function of the amounts of grafted HEMA, amount of grafted DMAEMA, initial pH value, and temperature. The adsorption capacity of the DMAEMA-grafted PE (PE-g-PDMAEMA) and (PE-g-PHEMA)-g-PDMAEMA plates had the maximum value at the initial pH value of 3.0, independent of the temperature. The adsorption capacity of (PE-g-PHEMA)-g-PDMAEMA plates increased with the amount of grafted HEMA (GHEMA ) in the first-step grafting. The increase in the water absorptivity of the grafted layers and thereby the increase in the degree of protonation of dimethylamino groups on grafted PDMAEMA chains were found to lead to the increase in the adsorption capacity. This adsorption capacity was higher than or comparable to those of other polymeric adsorbents for Cr(VI) ions. The Cr(VI) ion adsorption behavior on both PE-g-DMAEMA and (PE-g-PHEMA)-g-PDMAEMA plates obeyed the mechanism of the pseudo-second-order kinetic model and was well expressed by Langmuir isotherm. The high values of the Langmuir constant suggest that the adsorption of Cr(VI) ions occurs through an electrostatic interaction between protonated dimethylamino groups on grafted PDMAEMA chains andHCrO 4 − ions. Cr(VI) ions were successfully desorbed from PE-g-PDMAEMA and (PE-g-PHEMA)-g-PDMAEMA plates in eluents such as NaCl, NaCl containing NaOH, NH4 Cl, NH4 Cl containing NaOH, and NaOH.